The Use of Blended Data to Improve Public Assistance Programs: Results from a Partnership between the U.S. Census Bureau, USDA, and State Program Agencies - Cerf, Benjamin; Foster, Thomas B; Leach, Mark; Shattuck, Rachel (International Journal of Population Data Science, 2018)
The Census Bureau is partnering with state public assistance agencies to acquire program participation data and estimate new statistics that deepen a state’s understanding of program participants and improve outreach efforts to those who are eligible but do not participate. In collaboration with the Economic Research Service and the Food and Nutrition Service within the United States Department of Agriculture, the Census Bureau obtains individual-level program participation administrative records (AR) data for three state programs, the Supplemental Nutrition Assistance Program (SNAP), Temporary Aid for Needy Families (TANF), and the Special Supplemental Nutrition Program for Women, Infants and Children (WIC). The Census Bureau constructs a unique data set for each state program by linking the AR data to survey response data for the same individuals. These linked data enable the Census Bureau to model which survey respondents are eligible for program participation and also to observe which eligible individuals participate in the program. The Census Bureau then estimates eligibility and participation rates by a variety of demographic and economic characteristics and by county. The individual-level data also enable the Census Bureau to construct a statistical profile of eligible individuals and families that do not participate to assist state agencies with their outreach programs. All statistical results provided back to state agencies in table reports and data visualizations are reviewed to insure that individual identities are protected and not disclosed. This paper will present results for several state programs that have partnered the Census Bureau.